Development of Adrenocorticotrophic Hormone Cells of Adenohypophysis–Adrenal Cortex Axis of Long-tailed Monkey (Macaca fascicularis) during Pre and Postnatal Period - Nurhidayat Nurhidayat; Ika K. Syarifah; Supratikno Supratikno; Sri Wahyuni (Jurnal Kedokteran Hewan, 2008)
The objective of this study is to observe the relationship of development of adrenocorticotropic hormone (ACTH) cells of adenohypophysis–adrenal cortex axis during pre and postnatal period of longtailed monkey (Macaca fascicularis). Five fetuses aged 70, 85, 100, 120, and 150 days of gestation and 2new born aged 10 and 105 days old were used as research materials. The sections of the pituitary gland stained immunohistochemically using human ACTH antiserum and the adrenal glands stained by Hematoxylin-Eosin procedures. At the fetus 120 days old, the ACTH cells and blood vessel of fetaladenohypophysis developed well and its similar that found in older age. This condition suggested distributing the ACTH to whole body optimally. At the same time, the adrenal cortex cells of fetus 120 days old were active in proliferation and differentiation processes to form transition zone that lies between definitive and fetal zones, and central vein also developed in adrenal gland. In fetus aged 150 days, the cortex adrenal structure was similar with found in older fetus. The adenohypophysis ACTH cells developed earlier than adrenal cortex and their secretion suggested influencing the development of adrenal cortex cells of long-tailed monkey.